Comparative Practices of Campus Zakat Management: Evidence from Indonesia and Malaysia - Alfi Muhamad Ramdani; A'rasy Fahrullah Fahrullah; Najahudin Bin Lateh (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Campus zakat institutions play an increasingly important role in supporting student welfare in Muslim-majority countries; however, comparative evidence regarding effective zakat governance across university settings remains unexplored. This study aims to compare the management of campus zakat at Pusat Pengelolaan Dana Sosial (PUSPAS) of Universitas Airlangga, Indonesia, and Bahagian Zakat, Sedekah, dan Wakaf (ZAWAF) of Universiti Teknologi MARA, Malaysia, focusing on zakat collection, distribution, student empowerment, and institutional best practices. This study employed a qualitative research design using a phenomenological approach. Data were collected through interviews, observations, and document analysis to capture institutional experiences and practices in zakat management. The findings revealed significant differences in zakat collection mechanisms shaped by national legal frameworks. PUSPAS implemented a voluntary zakat collection system in accordance with Indonesian regulations, whereas ZAWAF applied a mandatory mechanism for Muslim contributors under Selangor state law. Despite these differences, both institutions developed student empowerment programs aimed at promoting long-term economic independence among mustahik students. The study highlights the importance of supportive regulations and sustainable empowerment strategies in optimizing campus zakat management to enhance student welfare.